The British American navigator [electronic resource] : a sailing directory for the island and banks of Newfoundland, the gulf and river of St. Lawrence, Breton Island, Nova Scotia and the coasts thence to Boston, etc. - Purdy, John, 1773-1843.; Findlay, Alexander George, 1812-1875. (London : Published for R.H. Laurie, 1862)
Includes publishers list. Includes index. Electronic reproduction. Mode of access: Internet. 44